Atomistic simulation of the obstacle strengths of radiation-induced defects in an Fe–Ni–Cr austenitic stainless steel. (26th September 2019) - Hesterberg, Justin; Smith, Richard; Was, Gary S
Abstract: A molecular dynamics method is employed to simulate the interaction of an edge dislocation with a combined solute cluster-dislocation loop defect, as well as independent faulted interstitial dislocation loops and solute clusters in an Fe–12Ni–20Cr at a temperature of 300 K. The examined defects are typical radiation-induced defects in austenitic stainless steels used as core structural components in nuclear reactors, while the selected composition matches with commercial grade 304L alloy. The dislocation-defect interaction is examined, and the peak shear stress required to overcome the obstacle array, and its dependence on obstacle size, solute concentration, and orientation is determined. The peak shear stress is then converted to an effective obstacle strength ( α ). Results show that dislocation loops are stronger obstacles than solute clusters, and their strength is heavily dependent on orientation, while the strength of solute clusters is largely dependent on the solute concentration. The total strength of the combined solute cluster-dislocation loop defect is largely contributed by the dislocation loop, though a fraction of the cluster strength is added as well.